2013
DOI: 10.1128/aac.01275-12
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Swabs Are Suitable for Quantifying the Carriage Load of KPC-Producing Carbapenem-Resistant Enterobacteriaceae

Abstract: It is more convenient and practical to collect rectal swabs than stool specimens to study carriage of colon pathogens. In this study, we examined the ability to use rectal swabs rather than stool specimens to quantify Klebsiella pneumoniae carbapenemase (KPC)-producing carbapenem-resistant Enterobacteriaceae (CRE). We used a quantitative real-time PCR (qPCR) assay to determine the concentration of the bla KPC gene relative to the concentration of 16S rRNA genes and a quantitative culture-based method to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 32 publications
2
38
0
8
Order By: Relevance
“…This may be relevant for clinical research because swabs are easier to obtain, on demand, than fecal samples. Recently, rectal swabs were similarly used to assess the RA of KPC-producing K. pneumoniae rather than DC (28).…”
Section: Discussionmentioning
confidence: 99%
“…This may be relevant for clinical research because swabs are easier to obtain, on demand, than fecal samples. Recently, rectal swabs were similarly used to assess the RA of KPC-producing K. pneumoniae rather than DC (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the possible presence in patient samples of DNA in dead cells could interfere with test results if performed before DNA degradation takes place. Nevertheless, in one study that evaluated whether rectal swabs are suitable for quantifying the carriage load of KPC-producing carbapenem-resistant Enterobacteriaceae , the authors found that the results of a quantitative PCR assay performed directly on rectal swabs showed a higher correlation than the quantitative culture-based method with the reference method (concentration of 16S rRNA genes), and that this quantitative PCR was suitable for quantifying these microorganisms [30]. In summary, our results need to be considered with caution and the strong correlation detected between Ct values and bacterial counts would need to be confirmed in clinical samples.…”
Section: Resultsmentioning
confidence: 99%
“…After incubating overnight at 37°C, the presence of an expanded growth inhibition zone between the two discs or increase of zone size of more than 7 mm in the disc potentiated with the EDTA (chelating agents) was interpreted as positive for MBL production All the tests and their interpretations were according to the CLSIGuidelines (M100 27 th edition 2017) and well-accepted methods by various authorities. (Lerner A et al, 2013, Rodrigues C et al, 2004, Neena V et al, 2012& Shamsadh Begum et al, 2015] the identity of the isolates and resistance pattern was further confirmed by using Vitek 2 GN ID (BioMerieux, France) with appropriate quality control. (Table 2).…”
Section: Modifiedmentioning
confidence: 98%
“…Rectal samples were collected in the sterile swab by inserting the swab 1cm into the rectum while rotating the swab. Rectal swabs are an appropriate alternative to stool specimens (Lerner et al, 2013). Total transit time to the laboratory was within 30 minutes.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation